Blocking TLR7- and TLR9-mediated IFN-α Production by Plasmacytoid Dendritic Cells Does Not Diminish Immune Activation in Early SIV Infection - Kader, Muhamuda; Smith, Amanda P.; Guiducci, Cristiana; Wonderlich, Elizabeth R.; Normolle, Daniel; Watkins, Simon C.; Barrat, Franck J.; Barratt-Boyes, Simon M. (PLoS pathogens, 2013)
Persistent production of type I interferon (IFN) by activated plasmacytoid dendritic cells (pDC) is a leading model to explain chronic immune activation in human immunodeficiency virus (HIV) infection but direct evidence for this is lacking. We used a dual antagonist of Toll-like receptor (TLR) 7 and TLR9 to selectively inhibit responses of pDC but not other mononuclear phagocytes to viral RNA prior to and for 8 weeks following pathogenic simian immunodeficiency virus (SIV) infection of rhesus macaques. We show that pDC are major but not exclusive producers of IFN-α that rapidly become unresponsive to virus stimulation following SIV infection, whereas myeloid DC gain the capacity to produce IFN-α, albeit at low levels. pDC mediate a marked but transient IFN-α response in lymph nodes during the acute phase that is blocked by administration of TLR7 and TLR9 antagonist without impacting pDC recruitment. TLR7 and TLR9 blockade did not impact virus load or the acute IFN-α response in plasma and had minimal effect on expression of IFN-stimulated genes in both blood and lymph node. TLR7 and TLR9 blockade did not prevent activation of memory CD4+ and CD8+ T cells in blood or lymph node but led to significant increases in proliferation of both subsets in blood following SIV infection. Our findings reveal that virus-mediated activation of pDC through TLR7 and TLR9 contributes to substantial but transient IFN-α production following pathogenic SIV infection. However, the data indicate that pDC activation and IFN-α production are unlikely to be major factors in driving immune activation in early infection. Based on these findings therapeutic strategies aimed at blocking pDC function and IFN-α production may not reduce HIV-associated immunopathology.